Learning organization : a study on the perceptions of organizational learning practices among Yemeni university librarians / Khaled Ateik Saeed Abdullah - Abdullah, Khaled Ateik Saeed (2007)
This study seeks to explore librarians perceptions of organizational learning practices in Yemeni university libraries, and its relationship with knowledge performance. Particularly, the study explores whether dimensions of learning organization based on the seven imperatives proposed by Watkins and Marsick are present independently and at the individual, team, and organizational levels in Yemeni university libraries, and to explore if there is a relationship between the learning organization dimensions and knowledge performance. The researcher translated into Arabic the Dimensions of the Learning Organization Questionnaire (DLOQ) for data collection. Data of the study were gathered from all 18 Yemeni university libraries (7 public and 11 private). A total of 198 respondents from both senior and middle-level librarians participated in this study with a response rate of 72%. For descriptive and inferential statistics, the researcher used the Statistical Package for Social Sciences (SPSS) version 13, while for Confirmatory Factory Analysis; Analysis of MOment Structures Statistical Program (AMOS) version 4.01 was used. The results of the study showed that the presence of learning practices were not enough to indicate that the Yemeni university libraries do have learning organization dimensions characteristics. The dimension with the highest average score was inquiry and dialogue (mean=4. 14) while the lowest dimension score was for empowerment (mean=3.23). The level of learning with the highest average score was team or group level (mean3.91) followed by individual level (mean3.81), and the lowest was organizational level (mean3.44). Correlation analysis showed that all seven dimensions (except enquiry and dialogue has weak relationship) have a moderately positive and significant relationship with knowledge performance at pvalue <0.01. Furthermore, the three levels of learning have moderate positive and significant relationship with knowledge performance at p-value < 0.01. The outcomes of this study will help Human Research Development practitioners, staff and leaders of Yemeni university libraries and their stakeholders in fostering their understanding of the importance of the learning organization and its correlation to knowledge performance.